THE COHESION OF TWO STUDENT GROUPS AND ITS IMPACT FOR LEARNING STRATEGIES AT ELEMENTARY SCHOOL - Agustina, Riza (Sunan Kalijaga International Journal on Islamic Educational Research, 2021)
Group cohesiveness is usually an interesting object of study in the context of social life and work management. However, cohesiveness can also be found in educational study areas. This study aims to determine the cohesiveness of the students of SD Negeri 2 Prambanan, find out the differences in cohesiveness between the independent groups and teacher formation groups, and the impact of the cohesiveness on the learning strategies. The quantitative methods are used to measure and to compare cohesiveness between the two groups using a t-test. The qualitative methods are used to narrate how teachers implement learning strategies according to student cohesiveness. The cohesiveness refers to the concept of Forsyth, which divides into the social, task, perceived, and emotional. This study finds that first, the group cohesiveness of students is in a moderate position. Second, the independent groups have significantly higher than the teacher formation groups. Third, there are five follow-ups in ​​learning strategies undertaken by the teacher, i.e. rearranging student seats, making students who have high group cohesiveness as group leaders, motivating students who have low cohesiveness to be actively involved in their groups, giving freedom to groups to compete, and applying various collaborative